Call center agents’ skills: Invisible, illegible, and misunderstood - Tovar, Johanna (Sociolinguistic Studies, 2021)
This article follows previous research arguing that skills of call center agents, which often include emotional labor, communication, procedural and substantive knowledge, and articulation work, are mostly invisible. Moving beyond previous analyses linking call centers to low-skilled standardized work, I draw on ethnographic fieldwork and transpositional analysis in the Philippines and the UK to show which real-world processes and written practices make agents’ skills not only invisible and illegible to industry outsiders but also to their managers. I argue that textualization practices such as data entry and script work are important, and that deemphasizing quantification in favor of qualitative assessment could produce better outcomes for agents and skill appreciation by others.